Acute toxicity of the synthetic pyrethroid deltamethrin to young mirror carp, Cyprinus Carpio - Çalta, Metin; Ural, Mevlüt Şener (My University, 2004)
In Turkey, mirror carps (Cyprinus carpio) are artifically reared and introduced to freshwater reservoirs, when they reached approx. 3-8 g body weight and a size range of 5-10 cm. At the same time, deltamethrin is commonly used for pest control in the agricultural fields surrounding freshwater reservoirs. So the acute toxicity of this synthetic pyrethroid, contaminating aquatic ecosystems as a potential toxic pollutant, was examined in this study. Young mirror carps sized from 3.5 to 5.8 g in weight and 6.2 to 7.4 cm in length were selected for the static bioassay test. Their cumulative mortality and 24, 48, 72 and 96-h LC50 values were determined. In addition, the behavior of these young carps at each deltamethrin concentration was observed. Data were assessed using the "Probity" statistical method. The 24, 48, 72 and 96-h LC50 values (95% confidence limit) for young mirror carp were estimated to be 9.41 (7.13-13.70), 4.47 (3.40-6.14), 2.37 (1.84-3.06) and 1.65 (1.32-2.07), respectively.
Keywords: Acute toxicity; Deltamethrin; Mirror carp (Cyprinus carpio); Pyrethroid